Epitaxial growth of γ-InSe and α, β, and γ-In2Se3 on ε-GaSe - Balakrishnan, Nilanthy; Steer, Elisabeth D.; Smith, Emily F.; Kudrynskyi, Zakhar R.; Kovalyuk, Zakhar D.; Eaves, Laurence; Patanè, Amalia; Beton, Peter H. (IOP Publishing, 2018)
We demonstrate that γ-InSe and the α, β and γ phases of In2Se3 can be grown epitaxially on ε-GaSe substrates using a physical vapour transport method. By exploiting the temperature gradient within the tube furnace, we can grow selectively different phases of InxSey depending on the position of the substrate within the furnace. The uniform cleaved surface of ε-GaSe enables the epitaxial growth of the InxSey layers, which are aligned over large areas. The InxSey epilayers are characterised using Raman, photoluminescence, X-ray photoelectron and electron dispersive X-ray spectroscopies. Each InxSey phase and stoichiometry exhibits distinct optical and vibrational properties, providing a tuneable photoluminescence emission range from 1.3 eV to ~ 2 eV suitable for exploitation in electronics and optoelectronics.